Applications of Omics Technology for Livestock Selection and Improvement - Chakraborty, Dibyendu; Sharma, Neelesh; Kour, Savleen; Sodhi, Simrinder Singh; Gupta, Mukesh Kumar; Lee, Sung Jin; Son, Young Ok (Frontiers in Genetics, 2022)
Conventional animal selection and improvement were based on the phenotypic performance of the animals. These methods have some limitations, particularly for sex limited traits and traits expressed later in the life cycle, like carcass traits. On these methods, genetic gain was less due to an increase in generation interval. However, new approaches using molecular breeding technologies came in existence to resolve these problems. With the advent of high-throughput techniques and the availability of multi-omics technologies along with sophisticated analytic packages, several promising tools and methods have been developed to estimate the actual genetic potential of the animals, and the task becomes very easy. It becomes easy to collect and access large and complex data sets consisting of different molecular, phonemics, physiological, and metabolic data as well as animal-level data (such as longevity, behavior, adaptation etc.), which provides new opportunities to understand better the mechanisms regulating animal’s actual performance. The cost of omics technology and expertise of several fields like biology, bioinformatics, statistics, and computer make these technology impediments to its use in many cases. The population size and accurate phenotypic data recordings are also major constraints for appropriate selection and breeding strategies. Because omics technologies estimate more accurate breeding values (EBVs) and increase the genetic gain by selecting the disease-free animals at an early stage of life cycle and enhancing animal productivity and profitability, these technologies are very popular for genetic selection, reproductive management, and breeding decisions of animals.